Centre for technology enabled creativity - Childs,PRN; Hamilton,T; Morris,RD; Johnston,G (The Design Society, 2007)
The Higher Education Funding Council for England (HEFCE), has recently awarded over £4 million (ca. 6 million Euro) to the University of Sussex and the University of Brighton to set up the Centre of Excellence in Teaching and Learning (CETL) in Creativity. The principal activities are the effective use of technology in the creative process with a particular focus, reflecting the collaboration between the two Universities involved, on engineering and design. This paper describes the pedagogic rationale behind this initiative and provides details of its implementation.